Case report: Primary cardiac angiosarcoma with multiple metastases - Li, Xuan; Lan, Lan; Hu, Huijuan (Frontiers in Cardiovascular Medicine, 2022)
We report a rare case of primary right atrial angiosarcoma with multiple metastases. Multimodality imaging and histopathology confirmed the diagnosis of primary cardiac angiosarcoma and multiple metastases. We present the details of the presentation, multimodality imaging findings, and clinical management. The patient was followed up by cardiac magnetic resonance imaging (CMRI) two months after therapy, the cardiac tumor and pulmonary metastases decreased markedly. Up to now, the patient has undergone four cycles of chemotherapy and immunotherapy.